2015
DOI: 10.1021/acs.chemmater.5b00112
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Doped Graphene Quantum Dots as an Ultrasensitive Redox Fluorescent Switch

Abstract: A new reversible fluorescent switch for the detection of oxidative hydroxyl radical (•OH) and reductive glutathione (GSH) was designed based on the use of selenium doped graphene quantum dots (Se-GQDs). The Se-GQDs have a thickness of 1–3 atomic layers, a lateral size of 1–5 nm, a quantum yield of 0.29, and a photoluminescence lifetime of 3.44 ns, which ensured a high selectivity and stability for the fluorescent switch. The fluorescence of Se-GQDs was reversibly quenched and recovered by •OH and GSH, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(117 citation statements)
references
References 74 publications
2
114
0
Order By: Relevance
“…Solvent optimization ( Table 1, entries [1][2][3][4][5][6][7][8][9] showed that toluene was the ideal solvent, while other reaction media gave significantly lower yields. Solvent optimization ( Table 1, entries [1][2][3][4][5][6][7][8][9] showed that toluene was the ideal solvent, while other reaction media gave significantly lower yields.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…Solvent optimization ( Table 1, entries [1][2][3][4][5][6][7][8][9] showed that toluene was the ideal solvent, while other reaction media gave significantly lower yields. Solvent optimization ( Table 1, entries [1][2][3][4][5][6][7][8][9] showed that toluene was the ideal solvent, while other reaction media gave significantly lower yields.…”
Section: Optimization Studiesmentioning
confidence: 99%
“…In this regard, post-modification is an alternative approach, in which GQDs can be modified by post-processing. 58,[60][61][62][63][64][65][66][67][68] Post-modification allows one to design GQDs with rationally improved properties. Polymer passivation is an often-adopted method to improve the quantum yield of GQDs.…”
Section: Post-modification Of Gqdsmentioning
confidence: 99%
“…Moreover, cancer cells can generate abundant H 2 O 2 compared to normal cells. Through Fenton reaction, H 2 O 2 can be activated by Fe 3+ /Fe 2+ to produce toxic hydroxyl radicals (•OH) (Equations and ), which can damage biological molecules to induce cell apoptosis . Furthermore, more •OH can be generated by recycling of Fe 2+ with irradiation of UV through Equation normalH2normalO2+Fe2+Fe3++OH+OHFe3++normalH2normalO2Fe2++HO2+normalH+FenormalOH2++hνFe2++OH…”
Section: Introductionmentioning
confidence: 99%